Novel POU3F4 variants identified in patients with inner ear malformations exhibit aberrant cellular distribution and lack of SLC6A20 transcriptional upregulation - Bernardinelli, Emanuele; Roesch, Sebastian; Simoni, Edi; Marino, Angela; Rasp, Gerd; Astolfi, Laura; Sarikas, Antonio; Dossena, Silvia (Frontiers in Molecular Neuroscience, 2022)
Hearing loss (HL) is the most common sensory defect and it affects 450 million people worldwide in a disabling form. Pathogenic sequence alterations in the POU3F4 gene, which encodes a transcription factor, are causative of the most common type of X-linked deafness (X-linked deafness type 3, DFN3, DFNX2). POU3F4-related deafness is characterized by a typical inner ear malformation, namely an incomplete partition of the cochlea type 3 (IP3), with or without an enlargement of the vestibular aqueduct (EVA). The pathomechanism underlying POU3F4-related deafness and the corresponding transcriptional targets are largely uncharacterized. Two male patients belonging to a Caucasian cohort with HL and EVA who presented with an IP3 were submitted to genetic analysis. Two novel sequence variants in POU3F4 were identified by Sanger sequencing. In cell-based assays, the corresponding protein variants (p.S74Afs*8 and p.C327*) showed an aberrant expression and subcellular distribution and lack of transcriptional activity. These two protein variants failed to upregulate the transcript levels of the amino acid transporter gene SLC6A20, which was identified as a novel transcriptional target of POU3F4 by RNA sequencing and RT-qPCR. Accordingly, POU3F4 silencing by siRNA resulted in downregulation of SLC6A20 in mouse embryonic fibroblasts. Moreover, we showed for the first time that SLC6A20 is expressed in the mouse cochlea, and co-localized with POU3F4 in the spiral ligament. The findings presented here point to a novel role of amino acid transporters in the inner ear and pave the way for mechanistic studies of POU3F4-related HL.